Deflagrations by design. Issue 4 (23rd April 2021) - Malik, Darren R.; Thomas, J. Kelly; Rodriguez, Oscar A.; Horn, Bradley J.; Geng, Jihui
Abstract: Large vapor cloud explosions (VCEs) and deflagration to detonation transition (DDT) events are of considerable interest to the petroleum refining and chemical processing industries. A detonation results in a very high flame speed and can significantly increase explosion energy and decrease standoff distance, increasing the blast load. Potential mitigation options to limit VCE severity include multiple simultaneous ignition sources to limit flame travel distance, suppressants to limit flame speed, and controlling the congested volume geometry to limit the flame travel distance. Another approach is minimizing the flame travel distance to free vent. Some VCE blast load prediction methods consider flame travel distance within a congested volume, but not the distance to free vent (DFV ). Decreasing the DFV limits flame acceleration and decreases the potential for a DDT. High fuel reactivities and elevated congestion/confinement levels require smaller distances to free vent. This paper describes a test program to demonstrate this mitigation option using near‐stoichiometric ethylene‐air mixtures in an elongated test rig configured with a medium level of congestion to determine the free vent distance required to prevent a DDT. Test program results, associated Flame Acceleration Simulator predictions, and potential areas for future research are included.